1999
DOI: 10.1046/j.1365-2265.1999.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin levels in women throughout pregnancy and the postpartum period and in women suffering spontaneous abortion

Abstract: Serum leptin concentrations rose slightly during pregnancy, fell following delivery and subsequently increased during the first six months postpartum. These variations were unrelated to changes in body composition, and may be responsible for the postpartum weight gain observed in some women. Abnormally low serum leptin levels were observed in women suffering spontaneous abortion in the first trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
1
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 41 publications
11
60
1
9
Order By: Relevance
“…First trimester cytotrophoblasts also contain leptin mRNA and protein and our studies suggest that placental leptin content increases from first to third trimester . This finding is in agreement with the gestational increase in leptin measured in the maternal circulation (Hardie et al, 1997;Lage et al, 1999). In addition, the leptin gene is also expressed in the villous vascular endothelial cells in direct contact with the fetal blood .…”
Section: Localizationsupporting
confidence: 80%
See 1 more Smart Citation
“…First trimester cytotrophoblasts also contain leptin mRNA and protein and our studies suggest that placental leptin content increases from first to third trimester . This finding is in agreement with the gestational increase in leptin measured in the maternal circulation (Hardie et al, 1997;Lage et al, 1999). In addition, the leptin gene is also expressed in the villous vascular endothelial cells in direct contact with the fetal blood .…”
Section: Localizationsupporting
confidence: 80%
“…During human pregnancy, circulating maternal concentrations of leptin increase to maximal values in the second trimester, plateau in the third trimester and fall to below pre-pregnancy concentrations around birth (Hardie et al, 1997;Lage et al, 1999). Although maternal fat deposition increases during pregnancy, changes in maternal body mass index appear not to correlate with the gestational increase in circulating leptin.…”
Section: Functionmentioning
confidence: 91%
“…As in many other studies (Butte et al, 1997;Lage et al, 1999;Sattar et al, 1998;Schrubing et al, 1998;Tamura et al, 1998), plasma leptin concentrations were signi®cantly higher in pregnant women when compared to non-pregnant women. Our study further indicated that this pregnancyrelated increase in leptin concentration starts within the ®rst 2 ± 3 weeks after conception.…”
Section: Discussionsupporting
confidence: 83%
“…(21) reported that leptin values increased significantly from the first to the second trimester, decreased slightly in the third trimester and declined markedly 4-6 weeks after delivery. Abnormally low serum leptin levels were observed in women suffering spontaneous abortion in the first trimester of pregnancy (29). In our study, serum leptin levels were similar in both groups.…”
Section: Discussionsupporting
confidence: 71%